Adipokines in bone disease - Neumann, Elena; Junker, Susann; Schett, Georg; Frommer, Klaus; Mueller-Ladner, Ulf (Nature Reviews Rheumatology, 2016)
Adipose tissue secretes highly bioactive factors, the adipokines. Systemic levels of adipokines are often altered in the presence of inflammation. In turn, adipokines affect different tissues and cells systemically as well as locally, contributing to immunomodulatory and bone remodelling mechanisms. The role of adipokines has been evaluated in chronic inflammatory diseases, such as rheumatoid arthritis, as well as in primarily degenerative joint diseases, such as osteoarthritis, particularly with regard to their levels of expression and their effects on joint tissues including synovial membrane, cartilage and bone. Distinct adipokines have been found to modulate matrix remodelling as well as inflammatory responses. In this Review, we summarize current knowledge relating to adipokines in rheumatic diseases, with a particular focus on the effects of adipokines on bone remodelling.
EVALuna2:13276